(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
The present article analyzes experiences of women in Self-managed work projects in the province of La Pampa. Several papers address the legal and administrative problematic issues that groups of workers face at the time of self managing their work projects. However, little has been said about the additional obstacles faced by women who try to formalize their entrepeneurship, which include gender inequality issues. Our work intends to be a gender-minded contribution, attending the intersection between work and social issues like class, gender and geographical region.